Safety, Tolerability, Pharmacokinetics, Target Occupancy, and Concentration‐QT Analysis of the Novel BTK Inhibitor Evobrutinib in Healthy Volunteers - Andreas Becker; Emily C. Martin; David Y. Mitchell; Roland Grenningloh; Andrew T. Bender; Julien Laurent; Harald Mackenzie; Andreas Johne (Wiley, 2020)
Bruton's tyrosine kinase (BTK) is a key regulator of B cell receptor and Fc receptor signaling, and a rational therapeutic target for autoimmune diseases. This first‐in‐human phase I, double‐blind, placebo‐controlled trial investigated the safety, tolerability, pharmacokinetics (PK), target occupancy, and effects on QT interval of evobrutinib, a highly selective, oral inhibitor of BTK, in healthy subjects. This dose escalation trial consisted of two parts. Part 1 included 48 subjects in 6 ascending dose cohorts (25, 50, 100, 200, 350, and 500 mg) randomized to a single dose of evobrutinib or placebo. Part 2 included 36 subjects in 3 ascending dose cohorts (25, 75, and 200 mg/day) randomized to evobrutinib or placebo once daily for 14 days. Safety and tolerability, as well as PK and target occupancy (total and free BTK in peripheral blood mononuclear cells), were assessed following single and multiple dosing. PK parameters were determined by noncompartmental methods. QT interval was obtained from 12‐lead electrocardiogram recordings and corrected for heart rate by Fridericia's method (QTcF). Treatment‐emergent adverse events (TEAEs) were mostly mild, occurring in 25% of subjects after single dosing, and 48.1% after multiple dosing. There was no apparent dose relationship regarding frequency or type of TEAE among evobrutinib‐treated subjects. Absorption was rapid (time to reach maximum plasma concentration (Tmax) ~ 0.5 hour), half‐life short (~ 2 hours), and PK dose‐proportional, with no accumulation or time dependency on repeat dosing. BTK occupancy was dose‐dependent, reaching maximum occupancy of > 90% within ~ 4 hours after single doses ≥ 200 mg; the effect was long‐lasting (> 50% occupancy at 96 hours with ≥ 100 mg). After multiple dosing, full BTK occupancy was achieved with 25 mg, indicating slow turnover of BTK protein in vivo. Concentration‐QTcF analyses did not show any impact of evobrutinib concentration on corrected QT (QTc). In summary, evobrutinib was well‐tolerated, showed linear and time‐independent PK, induced long‐lasting BTK inhibition, and was associated with no prolongation of QT/QTc interval in healthy subjects. Evobrutinib is, therefore, suitable for investigation in autoimmune diseases.